Aligning to disadvantage: How corporate political activity and strategic homophily create path dependence in the firm. (July 2021) - Perchard, Andrew; MacKenzie, Niall G
To what extent should firms get close to government for competitive advantage? What happens if they get too close? In this article we explore how corporate political activity inculcated strategic homophily in leading UK aluminium producer, the British Aluminium Company Ltd, resulting in its path dependence and eventual lock-in. The article makes three main contributions: a longitudinal study of corporate political activity and strategic homophily revealing their organizational manifestations and detailed understanding of certain mechanisms of path dependence; articulating the value of historical methods and perspectives to exploring organizational path dependence; and exploring the impact that prolonged business-government relations can have on the organizational behaviour and strategic outlook of the firm with implications for TMT selection and environmental scanning. In so doing it responds to calls for firms to align market positions with political activity, as well as those for the recognition of the value of business history in better understanding the links between corporate political activity and firm performance. It further elucidates the longer-term consequences of strategic homophily, which has to date focused on the early stages of venture formation.